Exchange coupling through diamagnetic [Fe(CO)4]2- bridging ligands in a xenophilic cluster. - Krämer, T; Lin, Z; McGrady, J (2011)
The electronic structure of so-called 'xenophilic' clusters, which contain both organometallic fragments and Werner-type paramagnetic transition metal centres, presents a challenge to simple theories of bonding. Density functional theory shows clearly that the cluster Mn(2)(thf)(4)(Fe(CO)(4))(2) is best described as an exchange-coupled Mn(II)(2) dimer, the closed-shell organometallic [Fe(CO)(4)](2-) fragments acting simply as bridging ligands. The high-spin configuration of the Mn(II) ions leads to single occupation of the Mn-Fe σ* orbitals and therefore substantially weaker metal-metal bonding than in conventional low-valent organometallic clusters. The transition metal fragments are effective mediators of superexchange (J(calc) = -44 cm(-1)), leading to the measured effective magnetic moment of ~5 μ(B) at 300 K, considerably lower than the limiting value of 8.37 μ(B) for two uncoupled S = 5/2 Mn(II) centres.